Implementasi Kebijakan Pengelolaan Dana Desa di Desa Pejambon Kabupaten Bojonegoro Jawa Timur - Diana Hertati; Lukman Arif (Journal of Economics, Business, and Government Challenges, 2018)
In the implementation of village funds, good governance is required to be appropriately targeted and be used for development and community empowerment. This research uses qualitative descriptive approach and data collection through observation and interview. Source of data by using porposive sampling assumed to have key informants, including: Sumberrejo Sub-district Head, Pejambon Village Head, BPD, secretary, treasurer, village apparatus, and community. Data analysis technique using interactive model. The results show that the implementation of Village Fund management in Pejambon Village involves the Technical Management Team of Village Financial Management (PTPKD). Indicators in determining accountability in implementation have been done well from openness to the use of funds.